Are the Exiting Quality of Life Measures Appropriate for Muslim Patients with Cancer? - Widyaningsih, Susana; Petpichechian, Wongchan; Kitrungrote, Luppana (Department of Nursing, Faculty of Medicine, Diponegoro University, 2013)
Purpose: This article aims to review the appropriateness of five general quality of life (QoL) measures for the Muslim patients with cancer.Method: The literatures related to QoL in patients with cancer, published between 1981 and 2011 were critically reviewed. Several database databases including CINAHL, MEDLINE as well as PUBMED, ProQuest, Elsevier, Google scholar and reference list were included. There were 25 articles best fit the inclusion criteria. Books and journal articles addressing Islamic principles were also reviewed.Result: QoL is a complex, multidimensional, and subjective phenomenon. It has been defined differently but overlapping by many scholars in the field. The patient’s QoL is important since it is one of the indicators of quality cancer care. The EORTC QLQ C30, FLIC, McGill QoL are the examples of widely used QoL measures which are appropriate to be applied in Muslim cancer population, while the FACT-G and CARES SF need to be revised in some of their items. Issues related to Islamic principles are discussed to support needs of further revision of these QoL measures.Conclusion: Most of the QoL measures’ items are not conflicting with the Islamic principles, except some items. Psychometric properties of the revised measures appropriate for Muslim cancer population should be further examined so that applying these measures can provide valid findings. Furthermore future cross cultural study may be possible.